PENINGKATAN KETERAMPILAN MENULIS PENGALAMAN PRIBADI MELALUI STRATEGI MODELLING - Ngudiana, - (WAHANA PEDAGOGIKA, 2016)
The election improve writing skills personal experience, has not been achieved against the backdrop of problems KKM basic competence 4.1 set of 74, 00 fifth-grade teachers. Based on interviews with teachers and students of fifth-grade, the causes of students get low marks for writing personal experiences are: 1) the students taught to make or study writing personal experience by giving assignment, 2) the students are not skillful enough to show or tell about their personal experience.The statement of problem from that case are: 1) how to improve process of improve writing skills personal experience by modeling strategy of fifth-grade students Elementary School Tondomulo 1, Bojonegoro? 2) How the improvement of writing skills personal experience of fifth-grade students Elementary School Tondomulo 1 by modeling strategy? Because of that, the purpose of research are: 1) to describe the improvement of skills personal experience by modeling strategy, 2) to describe the result of an improvement in the skill of writing personal experience of fifth-grade students Elementary School 1 Tondomulo by modeling strategy.